The Medicago truncatula hydrolase MtCHIT5b degrades Nod factors of Sinorhizobium meliloti and cooperates with MtNFH1 to regulate the nodule symbiosis - Li, Ru-Jie; Zhang, Chun-Xiao; Fan, Sheng-Yao; Wang, Yi-Han; Wen, Jiangqi; Mysore, Kirankumar S.; Xie, Zhi-Ping; Staehelin, Christian (Frontiers in Plant Science, 2022)
Nod factors secreted by nitrogen-fixing rhizobia are lipo-chitooligosaccharidic signals required for establishment of the nodule symbiosis with legumes. In Medicago truncatula, the Nod factor hydrolase 1 (MtNFH1) was found to cleave Nod factors of Sinorhizobium meliloti. Here, we report that the class V chitinase MtCHIT5b of M. truncatula expressed in Escherichia coli can release lipodisaccharides from Nod factors. Analysis of M. truncatula mutant plants indicated that MtCHIT5b, together with MtNFH1, degrades S. meliloti Nod factors in the rhizosphere. MtCHIT5b expression was induced by treatment of roots with purified Nod factors or inoculation with rhizobia. MtCHIT5b with a fluorescent tag was detected in the infection chamber of root hairs. Nodulation of a MtCHIT5b knockout mutant was not significantly altered whereas overexpression of MtCHIT5b resulted in fewer nodules. Reduced nodulation was observed when MtCHIT5b and MtNFH1 were simultaneously silenced in RNA interference experiments. Overall, this study shows that nodule formation of M. truncatula is regulated by a second Nod factor inactivating hydrolase in addition to MtNFH1.